Editors publishing in their own journals: A systematic review of prevalence and a discussion of normative aspects. Issue 2 (23rd February 2022) - Helgesson, Gert; Radun, Igor; Radun, Jenni; Nilsonne, Gustav
Abstract: Journal editors are the main gatekeepers in scientific publishing. Yet there is a concern that they may receive preferential treatment when submitting manuscripts to their own journals. The prevalence of such self‐publishing is not known, nor the consequences for reliability and trustworthiness of published research. This study aimed to systematically review the literature on the prevalence of editors publishing in their own journals and to conduct a normative ethical analysis of this practice. A systematic review was performed using the following databases: Medline, PsycInfo, Scopus and Web of Science. Articles that provided primary data about editors publishing in own journals were included. We identified 15 studies meeting inclusion criteria. There was large variability of self‐publishing across fields, journals and editors, ranging from those who never published in their own journal to those publishing extensively in their own journal. Many studies suffered from serious methodological limitations. Nevertheless, our results show that there are settings where levels of self‐publication are very high. We recommend that editors‐in‐chief and associate editors who have considerable power in journals refrain from publishing research articles in their own journals. Journals should have clear processes in place about the treatment of articles submitted by editorial board members.